2020
DOI: 10.1002/app.49692
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of oil‐ and water‐resistant paper without creating microplastics on disposal

Abstract: The proliferation of microplastics in the ocean and other water bodies is becoming an alarming issue. The development of plastic-free water-and oilresistant paper can contribute toward mitigating this problem. Herein we report a plastic-free paper coating derived from chitosan and sunflower oil. Chitosan grafted sunflower oil paper coatings were prepared via the ring opening of the partially epoxidized sunflower oil with chitosan. The product of these reactions was characterized by nuclear magnetic resonance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Various biopolymers from renewable resources like proteins, polysaccharides, lipids, and their combinations have been studied to explore their potential for various applications including paper coatings due to their numerous advantages such as biodegradability, biocompatibility, nontoxicity, recyclability, and low-cost compared to their conventional counterparts. However, paper coated with protein or polysaccharide-derived biopolymers lacks water resistance due to the hydrophilic nature of these coatings, which limits their desired performance in real-world applications. A dual-layer coating approach, which uses food-safe materials like chitosan with zein, chitosan with poly­(dimethylsiloxane) and zein (chitosan–PDMS–zein), and starch–zein has been reported to improve the moisture resistance and hydrophobicity properties of the coatings. Recently, Rabnawaz et al developed renewable hydrophobic chitosan-grafted sunflower oil-based coatings for paper substrates by treating partially epoxidized sunflower oil with chitosan, which resulted in 46% reduction in the water vapor transmission rate (WVTR) with a contact angle of 98.3°. Unlike proteins and polysaccharides, which are hydrophilic and can compromise the water resistance of paper coatings, lipids are hydrophobic in nature and are thus preferred for paper coating applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various biopolymers from renewable resources like proteins, polysaccharides, lipids, and their combinations have been studied to explore their potential for various applications including paper coatings due to their numerous advantages such as biodegradability, biocompatibility, nontoxicity, recyclability, and low-cost compared to their conventional counterparts. However, paper coated with protein or polysaccharide-derived biopolymers lacks water resistance due to the hydrophilic nature of these coatings, which limits their desired performance in real-world applications. A dual-layer coating approach, which uses food-safe materials like chitosan with zein, chitosan with poly­(dimethylsiloxane) and zein (chitosan–PDMS–zein), and starch–zein has been reported to improve the moisture resistance and hydrophobicity properties of the coatings. Recently, Rabnawaz et al developed renewable hydrophobic chitosan-grafted sunflower oil-based coatings for paper substrates by treating partially epoxidized sunflower oil with chitosan, which resulted in 46% reduction in the water vapor transmission rate (WVTR) with a contact angle of 98.3°. Unlike proteins and polysaccharides, which are hydrophilic and can compromise the water resistance of paper coatings, lipids are hydrophobic in nature and are thus preferred for paper coating applications.…”
Section: Introductionmentioning
confidence: 99%
“…A dual-layer coating approach, which uses food-safe materials like chitosan with zein, chitosan with poly(dimethylsiloxane) and zein (chitosan–PDMS–zein), and starch–zein has been reported to improve the moisture resistance and hydrophobicity properties of the coatings. 15 17 Recently, Rabnawaz et al 18 developed renewable hydrophobic chitosan-grafted sunflower oil-based coatings for paper substrates by treating partially epoxidized sunflower oil with chitosan, which resulted in 46% reduction in the water vapor transmission rate (WVTR) with a contact angle of 98.3°. Unlike proteins and polysaccharides, which are hydrophilic and can compromise the water resistance of paper coatings, lipids are hydrophobic in nature and are thus preferred for paper coating applications.…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al 13 prepared sodium alginate/hydroxymethyl cellulose and sodium alginate/propylene glycol alginate fluorine‐free barrier monolayer coatings, which were able to meet the oil resistance requirements of food packaging, while the lower surface energy improved the barrier properties to water, and the coatings improved the mechanical properties of the paper. Kansal et al 14 prepared biomass‐based coatings with good water and oil resistance by grafting chitosan on sunflower oil after epoxidation, and the results of the thermogravimetric analysis showed that the coated paper‐based material had excellent thermal stability at 250°C.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to reduce the production cost of barrier paper‐based materials, corn alcohol‐soluble protein can be mixed as a filler to reduce the use of chitosan and PDMS, which can also yield paper‐based materials with good barrier properties 16 . Kansal et al 14 used chitosan and corn alcohol‐soluble protein solutions for double coating, and the coated paper exhibited good barrier properties and thermal stability without affecting the mechanical properties of the paper. Subsequent validation of the recovery of the coated paper determined that the coating could be completely separated from the paper, facilitating pulp utilization and recovery of the coating material.…”
Section: Introductionmentioning
confidence: 99%
“…As one of biobased polymers, chitosan has also received attention. Dhwani et al [17] recently reported that the kit rating values of chitosan coated paper and chitosan-graft-sunflower oil coated papers were 12/12 and 8/12, in which the coating loads were 3.6 g/m 2 and 5.6 g/m 2 , respectively. Syeda et al [10] showed that the chitosan coated paper had a kit rating value of 12/12 when the coating load was 6.1 g/m 2 , and the chitosan-graft-polydimethylsiloxane coated paper obtained the eighth grade when the coating load was 9.4 g/m 2 .…”
Section: Introductionmentioning
confidence: 99%